2014
DOI: 10.15517/rbt.v53i3-4.14666
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology of <i>Oreochromis niloticus</i> (Perciformes: Cichlidae) at Emiliano Zapata dam, Morelos, Mexico

Abstract: Abstract:The reproductive season of tilapia was studied by monthly samplings at Emiliano Zapata dam, Morelos State, Mexico. From February 1999 through February 2000 a sample of 50 fish was taken from the commercial catch (castnet, 6.5 cm of mesh size). The observed sex ratio was 1:1.29 (females:males) (χ²=10.26; p<0.05). The tilapia reached maturity at 151.3 mm (females) and 152.0 mm (males) of total length. Rainy (August) and dry (February) seasons were determined as the breeding period. Fecundity variation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 15 publications
3
35
0
9
Order By: Relevance
“…However, they were described in six stages by Babiker and Ibrahim (1979), Duponchelle et al (1999Duponchelle et al ( , 2000, Komolafe and Arawomo (2007) and Mazrouh and Mahmoud (2009). Pena-Mendoza et al (2005) found three maturity stages of gonads of O. niloticus. These differences arises, because the sexual maturity is a function of the size and may be influenced by the abundance and seasonal availability of food, the temperature, the photoperiod and other environmental factors and pollution at different localities (Nikolsky, 1963;Babiker and Ibrahim, 1979;Pena-Mendoza et al, 2005).…”
Section: ------------------------------------------------------------mentioning
confidence: 91%
See 2 more Smart Citations
“…However, they were described in six stages by Babiker and Ibrahim (1979), Duponchelle et al (1999Duponchelle et al ( , 2000, Komolafe and Arawomo (2007) and Mazrouh and Mahmoud (2009). Pena-Mendoza et al (2005) found three maturity stages of gonads of O. niloticus. These differences arises, because the sexual maturity is a function of the size and may be influenced by the abundance and seasonal availability of food, the temperature, the photoperiod and other environmental factors and pollution at different localities (Nikolsky, 1963;Babiker and Ibrahim, 1979;Pena-Mendoza et al, 2005).…”
Section: ------------------------------------------------------------mentioning
confidence: 91%
“…Pena-Mendoza et al (2005) found three maturity stages of gonads of O. niloticus. These differences arises, because the sexual maturity is a function of the size and may be influenced by the abundance and seasonal availability of food, the temperature, the photoperiod and other environmental factors and pollution at different localities (Nikolsky, 1963;Babiker and Ibrahim, 1979;Pena-Mendoza et al, 2005). However, the investigation of the various maturity stages during the period of the present study showed that, ripe and spent males and females were encountered throughout the year with considerable varied frequencies between months to ensure preservation and not extermination of the species (Khallaf et al, 2003).…”
Section: ------------------------------------------------------------mentioning
confidence: 91%
See 1 more Smart Citation
“…Les ovules fécondés sont ensuite repris en bouche par la femelle pour incubation (Lacroix, 2004). La fécondité d'une femelle de tilapia est relativement faible et très variable en fonction du poids, des saisons, de la photopériode et de la concentration en chlorophylle a (CamposMendoza et al, 2004;Peterson et al, 2004;Peña-Mendoza et al, 2005). Une femelle pesant 100 g peut pondre environ 100 oeufs, alors que celle de 600 à 1000 g en pond 1 000 à 1 500 (Van Eer et al, 2004).…”
Section: Reproductionunclassified
“…Une femelle en bonnes conditions peut se reproduire avec une périodicité de 30 à 50 jours (Coward et Bromage, 2000). Une même femelle peut effectuer jusqu'à 10 pontes par an (Peña-Mendoza et al, 2005). La période la plus productive des géniteurs se maintient pendant les 12 premiers mois d'activité sexuelle (Peterson et al, 2004).…”
Section: Reproductionunclassified